2023
DOI: 10.1186/s12889-023-15128-6
|View full text |Cite|
|
Sign up to set email alerts
|

Non-optimal apparent temperature and cardiovascular mortality: the association in Puducherry, India between 2011 and 2020

Abstract: Background Cardiovascular diseases (CVDs), the leading cause of death worldwide, are sensitive to temperature. In light of the reported climate change trends, it is important to understand the burden of CVDs attributable to temperature, both hot and cold. The association between CVDs and temperature is region-specific, with relatively few studies focusing on low-and middle-income countries. This study investigates this association in Puducherry, a district in southern India lying on the Bay of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…At present, little is known on CVD impacts of climate change in India. Our related study from Puducherry found a high attributable burden of non-optimal temperature to CVD mortality, suggesting a need for similar studies from around the country [65,66]. The CVD specific challenges we identified here are comparable to the general health challenges.…”
Section: Discussionsupporting
confidence: 61%
“…At present, little is known on CVD impacts of climate change in India. Our related study from Puducherry found a high attributable burden of non-optimal temperature to CVD mortality, suggesting a need for similar studies from around the country [65,66]. The CVD specific challenges we identified here are comparable to the general health challenges.…”
Section: Discussionsupporting
confidence: 61%
“…Worker productivity decreases when the Wet Bulb Global Temperature (WBGT) is above 26 to 30 °C [ 62 ]. Puducherry, with an average temperature of 30 °C, has an apparent temperature range between 23 and 41 °C, meaning it is especially important to protect the health of outdoor workers such as farmers, fishermen, construction and manual labourers [ 63 , 64 ]. Policy measures to reduce workplace heat exposure in the context of climate change and improve occupational health are imperative to protect the working population, as has also been recommended by WHO [ 60 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…19,22,29 A study from India showed that females both above and below 60 years of age, on average, have a higher risk of CVD mortality from heat than men. 29 Similarly, a study from São Paulo, Brazil, showed a higher risk of overall CVD-related deaths in females during heat waves compared with men. 22 Other evidence was also reported from European countries, 25,35 United States, 19 China, 18,34 and Australia, 56 A greater risk of heat-related CVD mortality was also observed in studies from LMICs than in upper…”
Section: Susceptible Groups For Climate Effectsmentioning
confidence: 99%
“…Although some studies have shown a higher risk in males, 21 several studies have found higher susceptibility in females. 19 , 22 , 29 A study from India showed that females both above and below 60 years of age, on average, have a higher risk of CVD mortality from heat than men. 29 Similarly, a study from São Paulo, Brazil, showed a higher risk of overall CVD-related deaths in females during heat waves compared with men.…”
Section: Susceptible Groups For Climate Effectsmentioning
confidence: 99%